Optimalisasi Nilai-Nilai Keagamaan di Lingkungan Masyrakat Desa Ujung Karang - Mas Agus Abdul Rahman Ramadhan; Taufik Riyadi; Bintang Riski Illahi; Persi; Rere Melaningsi; Eka Olivia Fitri; Rice Elma Nengsi; Tri Hennarti Daulay; Ferdia Ardianti; Kiki Santika (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
Religion plays an important role in society. This is realized through religious activities, including recitation, teaching and habituation. Religious activities aim to optimize and foster religious values in individuals, both adults and children. During community service activities, especially in Ujung Karang village, we held religious activities, namely children’s recitations at the local mosque, namely the Ash-Shihab Mosque. The aim is to attract children’s interest so that they can return to regular recitation activities which had faded. As for religious activities among adults, they are going quite well. There are recitation activities that are routinely carried out in various assemblies. This can show the high religious values of the community in Ujung Karang village. It is hoped that the contribution from KKN students can further optimize religious activities in the Ujung Karang village environment, especially to foster children’s interest in taking part in recitation activities